2013 IEEE 24th International Symposium on Software Reliability Engineering (ISSRE) 2013
DOI: 10.1109/issre.2013.6698918
|View full text |Cite
|
Sign up to set email alerts
|

Got issues? Who cares about it? A large scale investigation of issue trackers from GitHub

Abstract: Abstract-Feedback from software users constitutes a vital part in the evolution of software projects. By filing issue reports, users help identify and fix bugs, document software code, and enhance the software via feature requests. Many studies have explored issue reports, proposed approaches to enable the submission of higher-quality reports, and presented techniques to sort, categorize and leverage issues for software engineering needs.Who, however, cares about filing issues? What kind of issues are reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 23 publications
1
88
0
3
Order By: Relevance
“…Issues can be bugs, feature requests, enhancements and other types of reporting related to a repository [21] [22].…”
Section: Oss Hosting Platformsmentioning
confidence: 99%
See 3 more Smart Citations
“…Issues can be bugs, feature requests, enhancements and other types of reporting related to a repository [21] [22].…”
Section: Oss Hosting Platformsmentioning
confidence: 99%
“…Moreover, JavaForge has as well announced on March, 2016 that it will be shut down permanently [25]. Among the 10 platforms that were selected, GitHub is the largest one hosting the largest number of OSS projects [19], [20], [22], [35]. Other platforms such as Bitbucket, Gitlab, Codeplex and SourceForge are also popular platforms.…”
Section: Selected Oss Hosting Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“…Every commit was automatically checked whether the word "bug" was in the commit header or the commit message. The term "bug" was used because a large-scale study on tens of thousands of GitHub software projects (Bissyande et al 2013) found out that the most popular tag used in GitHub issue reports is bug. Hence, we think that most programmers also use the term bug to commit defects.…”
Section: Data Collection Proceduresmentioning
confidence: 99%